Vibration serviceability of special footbridges in South Africa: an investigation of the crowd capacity of the Boomslang canopy walkway - Ragoleka, Itumeleng (Department of Civil Engineering, 2020)
The vibration serviceability of footbridges subjected to pedestrian loading has been an academic pursuit since the year 1850 (Fujino & Siringoringo, 2015). Initially, research was focussed on understanding the influence of pedestrian vertical loading on the dynamic behaviour of a footbridge. Furthermore, this loading was investigated in the context of the comfort experienced by the pedestrian on the bridge. The conclusion was that although the contribution of the vertical load is significant, synchronization and lock-in of pedestrians in this direction is difficult to achieve and thus minimal effect is imposed on the comfort of the pedestrian. More prominently, research on the lateral component of the pedestrian-induced force was conducted after the observed vibration serviceability issues on the London Millennium bridge (Dallard, Fitzpatrick, et al., 2001b). Research showed that although the contribution of the lateral component is minute (i.e 5%) (Zivanovic, Pavic & Reynolds, 2005), it is significant in its influence on the lateral dynamic behaviour of a footbridge and subsequently, the comfort experienced by the pedestrian. A valuable result from these investigations was the stability criterion (i.e the Arup model) derived by Dallard, Flint, et al. (2001). The premise of the result is that pedestrians induce negative damping to the bridge system, therefore, there exists a critical number of pedestrians who collectively induce a force which eliminates the inherent positive damping of the footbridge system and triggers synchronization or lock-in which results in excessive lateral vibrations. Consequently, excessive lateral vibrations result in diminished comfort levels. The critical number of pedestrians required to trigger lock-in is influenced by the modal dynamic parameters of the footbridge; i.e, natural frequency, modal mass and modal damping ratio. Conventionally, these parameters are presented in static form, however, this omits valuable information about the dynamic behaviour of the structure. A few advances, such as the short time fourier transform and the synchrosqueezed wavelet transform, have been made to present the modal parameters in a dynamic form. However, much of literature only presents the frequency content in dynamic form and leaving the modal mass and modal damping in static form. Therefore, the aim of this thesis was to perform crowd investigations on the Boomslang Canopy walkway, and determine the critical number of pedestrians required to trigger lock-in on the bridge using the Arup model and the vibration comfort limit method. Another aim of this thesis was to either support or challenge the convetional notion that SLE is the initiating mechanism of excessive lateral vibrations on a footbridge. The Arup model and the vibration comfort limit method were found to compute different results regarding the critical number of pedestrians. Beyond this, the obtained vibration data and the synchrosqueezed wavelet transform analysis of this data showed evidence contrary to the popular assumption that SLE is the intiating mechanism for excessive lateral vibrations. Ultimately, the results showed that the Boomslang is a lively bridge and that the potential for SLE and lock-in on the bridge is highly probable.